PENGAKUAN DAN KEWARISAN ANAK LUAR NIKAH MENURUT PRESPEKTIF HUKUM PERDATA (BW), HUKUM ADAT DAN KOMPILASI HUKUM ISLAM - Thoib Thoib; Ibnu Jazari; Dzulfikar Rodafi (Jurnal Hikmatina, 2020)
AbstrakMarriage is one form to get an offspring which later in order to get a successor who could someday replace his position for his offspring, but in matters of descent sometimes it is not easy that we expect but many obstacles and problems that often occur in the real world.About discussing offspring is nothing but going to discuss about inheritance and legal recognition, this problem arises when there is a lover who gets offspring but does not go through a legal process according to civil law, customary law or Islamic law.With this study trying to illustrate the comparison of recognition and inheritance of out-of-wedlock children from three perspectives, namely: civil law (BW), customary law and compilation of Islamic law.Thus, researchers can find out from the three existing laws to elaborate on specific designs, normative research is applied in this study, besides normative research is research that uses literature or sources derived from articles, journals, the Qur'an , The Book of the Law, the Hadith, Opinion of jurists and also opinions of jurists or competent Islamic law as research.Keyword : recognition, inheritance, extramarital children